Utilization and access to metered-dose inhalers and sustainable alternatives among older adults in the United States: a population-based studyResearch in context - Ashwaghosha Parthasarathi; Isao Iwata; Catherine Chen; Amy R. Li; Novella Lye; Poonam Gandhi; Melanie Rua; Reynold A. Panettieri, Jr.; Jared Radbel; Mahesh Padukudru Anand; Mary Bridgeman; Soko Setoguchi (The Lancet Regional Health. Americas)
Summary: Background: Attaining the Paris Agreement goal of limiting global temperature rise to below 1.5–2 °C requires the healthcare sector to achieve net-zero emissions by 2050. This necessitates adopting diverse strategies, including replacing carbon-intensive metered-dose inhalers (MDIs) with more environmentally sustainable dry powder inhalers (DPIs) and soft mist inhalers (SMIs). While several European countries have successfully made this transition, patterns of MDI use and barriers to adopting sustainable alternatives in the United States remain poorly understood. Thus, we assessed inhaler utilization, costs, and insurance coverage among U.S. older adults. Methods: Using 100% fee-for-service Medicare data with pharmacy benefit (2008–2022), we described utilization trends and costs by device types and drug classes, including inhaled corticosteroids [ICS] and short-/long-acting beta-agonists [S/LABA]. Using the COVERAGE Search database, we extracted formulary data from Part D plans in 10 large US states and described insurance coverage, formulary tier placement (categorizing drugs by costs), prior authorization (requiring insurer approval for coverage), and step therapy (requiring initial trial of lower-cost drugs). Findings: Of 160,845,280 inhalers dispensed to 10,494,068 older adults (mean age 74 ± 7 years; 38% male; 85% White), 51% were MDIs. Of these MDIs, 88% were SABA and ICS. Median deductible-phase out-of-pocket costs were $3–9 for SABA MDIs vs. $42–49 for DPIs/SMIs and $3–4 for ICS MDIs vs. $3–116 for DPIs/SMIs. Only 18% and 50% of 2530 Part D plans covered SABA and ICS DPIs, respectively. Among the covering plans, >70% placed DPIs for SABA or ICS in higher-cost tiers, with 32–58% requiring prior authorization or step therapy. Interpretation: MDIs, primarily as SABA or ICS, accounted for over half of inhalers dispensed to US older adults. Most insurance plans excluded sustainable alternatives for SABA/ICS. When covered, additional approval steps and/or higher patient costs were posed. Multi-level efforts are needed to ensure affordable access to sustainable alternatives, as demonstrated in European countries. Funding: Funding for this study was provided by the National Institutes of Health and the National Institute on Aging (1R01AG060232-01A1).